Called to justice : the life of a federal trial judge - Urbom, Warren K. (Law in the American West., 2012)
Early in his judicial career, U.S. District Judge Warren K. Urbom was assigned a yearlong string of criminal trials arising from a seventy-one-day armed standoff between the American Indian Movement and federal law enforcement at Wounded Knee, South Dakota. In Called to Justice Urbom provides the first behind-the-scenes look at what quickly became one of the most significant series of federal trials of the twentieth century. Yet Wounded Knee was only one set of monumental cases Urbom presided over during his years on the bench, a set that in turn forms but one chapter in a remarkable.